KERALA PATTERN AND MORAL INVERSION: A Historical Review of the Communist Strategy in Light of Polanyian Theory - Thekkemuriyil Antony, Mathew (Asian Horizons, 2017)
To be a dispassionate critic of the society, one has to learn its undercurrents while pruning it with bold criticism. Moral inversion is a theory developed by the Hungarian-British polymath Michael Polanyi (1891-1976), which according to him, is the fusion of skepticism and utopianism. The modern mind, says Polanyi, is suffering from two major diseases consisting of two wrong principles. First is the view that “detached objectivity or explicitness as the ideal of knowledge” and the second, “perfectionism as the ideal in moral and social concerns.” He observes that together these two ideals contribute to moral inversion. In the phenomenon of moral inversion, good is lost due to the unrealistic commitment to the good. Polanyi believes, as a moral philosopher, that a “universal mechanical interpretation of things […] impairs man’s moral consciousness” and effects an “absolute moral neutrality of science.” Polanyi develops his theory of moral inversion always in reference to communism. This article is an attempt to read the communist strategy in the South Indian state of Kerala in light of the social and political thoughts of Michael Polanyi with the help of the Polanyian tool of moral inversion.